2020
DOI: 10.1111/ijfs.14711
|View full text |Cite
|
Sign up to set email alerts
|

Post‐harvest physiological deterioration in several cassava genotypes over sequential harvests and effect of pruning prior to harvest

Abstract: Consumers, traders and processors consider post-harvest physiological deterioration (PPD) an important constraint. In Experiment 1, PPD was assessed three consecutive years in roots from five genotypes through seven storage days. PPD, scopoletin and dry matter content (DMC) was recorded during storage. Year, genotype, duration of storage and their interactions were significant. PPD was associated with duration of storage period, DMC and scopoletin contents. Ambient moisture and temperature during storage influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
5
27
0
Order By: Relevance
“…These varieties would take three to five days before showing visible signs of PPD. This observation concurs with reports from several authors who reported variations among varieties for PPD [12,14,17,[33][34][35]. Some varieties could go up to 40 days with no visible PPD signs [14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These varieties would take three to five days before showing visible signs of PPD. This observation concurs with reports from several authors who reported variations among varieties for PPD [12,14,17,[33][34][35]. Some varieties could go up to 40 days with no visible PPD signs [14].…”
Section: Discussionsupporting
confidence: 93%
“…The results complement those in literature that effective control and preventative measures for PPD should properly integrate the following five strategies: (i) modifying storage conditions; (ii) improving processing of fresh cassava roots; (iii) selection of tolerant genotypes; (iv) pre-conditioning cassava tissue before harvesting; and (v) preventing active gene expression during storage. Some of these strategies can be combined [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saravanan et al [90] reported that the estimated yield losses of fresh cassava roots due to PPD are nearly a third of the total harvest worldwide. The expression of PPD is controlled by genotypic and environmental factors following microbial infections [91]. In Thailand where cassava is the most important industrial crop, PPD results in an economic loss of up to USD 35 million annually [92].…”
Section: Post-harvest Physiological Deterioration (Ppd)mentioning
confidence: 99%
“…fr) is an ambitious initiative to elucidate basic information regarding root quality traits. Several research articles regarding root quality traits and post-harvest processing have recently been published (Alamu et al 2021;Bechoff et al 2018;Dufour et al 2021;Escobar et al 2021;Goddard et al 2015;Iragaba et al 2021;Luna et al 2021;Ndjouenkeu et al 2021;Teeken et al 2018Teeken et al , 2021Thiele et al 2021;Tran et al 2021). The availability of this critical knowledge and reliable high-throughput phenotyping protocols will improve the efficiency of breeding for root quality traits.…”
Section: Understanding and Dissecting Quality Traits For Human Consumptionmentioning
confidence: 99%